Gut microbiota analysis in cirrhosis and non-cirrhotic portal hypertension suggests that portal hypertension can be main factor of cirrhosis-specific dysbiosis - Kseniya Gulyaeva; Maria Nadinskaia; Roman Maslennikov; Yulia Aleshina; Irina Goptar; Alexander Lukashev; Elena Poluektova; Vladimir Ivashkin (Scientific Reports)
Abstract Gut dysbiosis plays an important role in cirrhosis, but the mechanism of its development was not established. The aim of the study was to test the hypothesis that portal hypertension can be the main factor in the development of gut dysbiosis in cirrhosis. This cross-sectional study included 25 patients with chronic non-cirrhotic portal hypertension due to extrahepatic portal vein obstruction after portal vein thrombosis (PVT) (NCPVT group), 29 cirrhotic patients without PVT (CirNoPVT), 15 cirrhotic patients with chronic PVT (CPVT), and 22 healthy controls. The fecal microbiota was assessed using 16S rRNA gene sequencing. The CirNoPVT and CPVT groups had largely similar differences in gut microbiota composition from the control group. Patients with NCPVT, as well as patients with cirrhosis, had a higher abundance of Streptococcus, Escherichia, Enterococcus, Enterobacteriaceae, Enterococcaceae, Streptococcaceae, Bacilli, Gammaproteobacteria, Proteobacteria, and a lower abundance of Roseburia, Faecalibacterium, Methanobrevibacter, Ruminococcaceae, Methanobacteriaceae, Clostridia, Methanobacteria, and Euryarchaeota as they were compared with healthy individuals. Patients with NCPVT had a higher abundance of Bifidobacterium, Bifidobacteriaceae, Actinobacteria, and a lower abundance of Gemmiger and Catenibacterium compared to healthy individuals, which was not observed in the cirrhosis groups. The abundance of Porphyromonadaceae with the genus Parabacteroides was reduced in both groups with PVT, but not in CirNoPVT. There were no significant differences in gut microbiota beta-diversity among the CirNoPVT, CPVT and NCPVT groups. All these groups had significant differences in beta-diversity from the control group. Portal hypertension seems be the main factor in the development of gut dysbiosis in cirrhosis.